The development of emotional intelligence and its influencing psychological factors among students majoring in english language teaching - Rustamova Munisa Tulqin Qizi (Psychohealth: Scientific Journal of Psychology and Mental Health, 2026)
Purpose: This study analyzes psychological and social factor scontributing to occupational stress among military personnel,focusing on key stressors, their impact on mental health and operational performance, and potential stress managementstrategies. Methodology: A mixed-methods design was applied, combining theoretical review and empirical analysis. Data were obtainedfrom 100 military personnel using questionnaires, the Holmes Rahe Life Stress Inventory, COPE Inventory, Spielberger’s State-Trait Anxiety Inventory, interviews, and direct observations. Data were analyzed through descriptive statistics, correlation analysis,and thematic analysis. Results: The findings show that more than 65% of respondents experience moderate to high stress levels. Major stressors includeorganizational pressure, family separation, and strict disciplinary systems. Coping strategies are mostly avoidance-based andemotional withdrawal, while problem-focused coping is less common. High anxiety levels indicate insufficient psychologicalsupport and limited adaptive coping mechanisms. Conclusion: Occupational stress among military personnel is strongly influenced by both organizational and personal factors,requiring structured psychological interventions and supportive institutional policies. Limitations: The study is limited to a single sample group and relies on self-reported data, which may introduce bias.Contributions: This research contributes to military psychology by identifying key stressors and providing evidence-basedrecommendations for stress management and institutional support programs.